Analysis of the main geometrical characteristics that affect the bonding of ribs in rebars thinly covered to repair masonry structures. (1st November 2021) - Rodriguez-Mayorga, Esperanza; Hortigon, Beatriz; Ancio, Fernando
Graphical abstract: Highlights: Bonding in 5-mm stainless-steel rebars embedded in a hydraulic medium is analysed. Microplane theory reproduces behaviour of a hydraulic medium in Finite Element Method. Bonding is evaluated by Finite Element Method defining a Cohesive Zone Model. Multi-linear regression enables results to be extended over a larger set of samples. The most influential geometric features of ribs in bonding behaviour are ascertained. Abstract: The use of stainless steel rebars in the repair of masonry structures is widespread and has traditionally produced excellent results. In these cases, rebars usually present diameters of below 8 mm covered with thin layers of mortar or grout. Research is necessary to characterise bonding under these particular conditions, hitherto unavailable. In this research, the geometry of ribs is parameterised and later analysed through the Finite Element Method. To this end, the Microplane model and Cohesive zone model are employed. Based on the numerical results, the geometrical aspects of the ribs that mostly affect bonding are identified and discussed.